State: Theoretical-Descriptive Proposal on a New and Unknown Verbal Accident - Vásquez González, Jorge Alberto (2020)
After distinguishing between the simple tenses and the respective compound tenses of the verbal conjugation of Spanish in three moods (indicative, potential, and subjunctive) and assuming new qualities of the grammatical aspect (continuous and discontinuous, unlike the traditional perfect and imperfect), the article proposes to establish a new verbal accident: state. It would be added to the six accidents commonly recognized in the grammar: voice, mood, tense, aspect, person, and number. The morphematic nature of the state differs from the morphematic nature of the aspect: there would be a decisive criterion to differentiate these two concepts. The article also explains that the non-personal forms of the verb (infinitive, gerund, and participle) have in particular the state morpheme. It concludes with a new model and terminology of verbal conjugation.